-3(w-3)=7w+39

Simple and best practice solution for -3(w-3)=7w+39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(w-3)=7w+39 equation:


Simplifying
-3(w + -3) = 7w + 39

Reorder the terms:
-3(-3 + w) = 7w + 39
(-3 * -3 + w * -3) = 7w + 39
(9 + -3w) = 7w + 39

Reorder the terms:
9 + -3w = 39 + 7w

Solving
9 + -3w = 39 + 7w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-7w' to each side of the equation.
9 + -3w + -7w = 39 + 7w + -7w

Combine like terms: -3w + -7w = -10w
9 + -10w = 39 + 7w + -7w

Combine like terms: 7w + -7w = 0
9 + -10w = 39 + 0
9 + -10w = 39

Add '-9' to each side of the equation.
9 + -9 + -10w = 39 + -9

Combine like terms: 9 + -9 = 0
0 + -10w = 39 + -9
-10w = 39 + -9

Combine like terms: 39 + -9 = 30
-10w = 30

Divide each side by '-10'.
w = -3

Simplifying
w = -3

See similar equations:

| 2n(n+5)=-4(n+5) | | 11x+25y=180 | | -20y=25y | | 2y-4=-3(y+8) | | 7n^2-35n-98=0 | | 25y=50 | | 15/60=n/6 | | 25=50 | | (2x+40)*(x+6)=4x^2 | | 2x+1=9x-1 | | 0.25(5+x)+0.75(x+1)=2.5 | | 2(w+6)=-7+30 | | F(6)=8 | | 4n^2-16n=44 | | 15+6r=7(4r-1) | | 2(w+6)=7w+30 | | x+70=2x | | 4.5x=100 | | (3x+20)(x-10)=0 | | x+1=2x+12 | | -144=-12r | | 3i(8+5i)=0 | | 5/x-3cosx | | 5x/12=1 | | 15+6t=7(4r-1) | | g/-16 | | 2x+8=3+2x | | 2(x+h)+k=8 | | 5z^2-20+15=0 | | 135x-59= | | (5*x-15)/2=10 | | 7=4tan(2x-1) |

Equations solver categories